Benang Bintik: Sebuah Eksplorasi Nilai Filosofis dan Konsep Matematis dengan Pendekatan Etnomatematika - Rahmawati, Laila; Rafsanjani, Muhamad Arief; Dilla, Widya Permata; Pebrianti, Tria (FKIP Universitas Palangka Raya, 2025)
Innovative mathematics education plays a crucial role in providing meaningful learning experiences. This approach can be realized by linking mathematical concepts to everyday situations, making the learning process more relevant and engaging for students. One approach that can be applied is introducing local cultural values, which are reflected in the integration of cultural elements into mathematics education. This process is known as ethnomathematics. Ethnomathematics-based learning can be seen in various motifs of Benang Bintik batik, which is a distinctive feature of the batik from Central Kalimantan Province. This research is exploratory, aimed at discovering the factors that influence the occurrence of a phenomenon or to understand the research object more deeply. The study was conducted at the Batik Benang Bintik Paramita production house located on Badak XXV Street, Bukit Tunggal Subdistrict, Palangka Raya City. Data was collected through observation, interviews, and documentation. The results revealed information about the production process of stamped and hand-drawn batik, as well as some of the philosophies embedded in the Benang Bintik batik motifs. The philosophies in these motifs include hopes to God or ancestors, humans, and other creatures (the balanga motif); depictions of the three levels of the universe according to the beliefs of the Dayak Ngaju tribe (the batang garing motif); symbols of courage, protection, strength, and Dayak identity (the talawang motif); the bond between humans (the kalalawit and bajakah kalalawit motifs); and nobility and protection (the enggang bird motif). Additionally, the Benang Bintik motifs also contain mathematical concepts such as points, lines, angles, flat shapes, and geometric transformations. Therefore, these motifs can be used as innovative, contextual learning media for mathematics, while supporting the preservation of local culture.